Factors Affecting the Teaching and Learning Process According to Islamic Education Philosophy - Sabrina, Rifdah; Kakoh, Nur Asikin; Rahman, Ikhwan; Izzati, Reska Zhuria; Patmawati, Patmawati; Fitri, Rika (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
The teaching and learning process in the perspective of Islamic education is influenced by various factors involving intellectual, spiritual, social, and physical aspects. This study aims to identify the main factors that influence the teaching and learning process according to the philosophy of Islamic education. This study uses the Systematic Literature Review method. With this research method, the researcher reviews and identifies journals systematically in the Google Scholar database and several online books. The literature analysis shows that the factors found include spiritual aspects and sincere intentions in learning, harmonious relationships between teachers and students, a conducive educational environment, and teaching methods that prioritize dialogue and a humanistic approach. Additionally, motivational factors stemming from the intention to seek knowledge for the benefit of both this world and the hereafter, parental and community involvement, and the importance of teaching ethics and character also play a significant role in shaping educational success. The results of the study show that Islamic educational philosophy emphasizes a balance between the aspects of reason and heart in the learning process, which aims not only to acquire knowledge but also to shape noble character in each individual. This study also provides insight into how these factors interact in shaping an effective and meaningful teaching and learning process.